Joy of agility : how to solve problems and succeed sooner - Kerievsky, Joshua (Ascent Audio, 2023)
Agility enables you, your team, and your organization to streamline slow and awkward actions, overcome obstacles quickly, and adapt to change with ease and grace. Agility isn't a formula, a framework, nor a set of roles and rituals to follow. It's a timeless way of being that matures with practice and skill. Becoming agile involves knowing the difference between being quick or hurrying, moving with ease or difficulty, being in or out of balance, graceful or awkward, adaptable or rigid, resourceful or resentful. With Joy of Agility, Joshua Kerievsky, CEO of Industrial Logic, one of the oldest and most-respected agile consultancies in the world, shows you how to harness agility in work and life to solve problems and succeed sooner. Kerievsky shares six essential agile mantras, plus unforgettable, real-world stories of agile people and teams, that will empower you to be quick, adaptable, and resourceful in the face of challenges and opportunities. Learn how to: distinguish between being quick and hurrying; gain better balance and collaborate gracefully with others; prepare and practice being poised to adapt; take deliberate steps to drive out fear; grow a solution by starting minimal and evolving; and overcome obstacles by being readily resourceful.